2011
DOI: 10.1186/1748-5908-6-40
|View full text |Cite
|
Sign up to set email alerts
|

Shared communication processes within healthcare teams for rare diseases and their influence on healthcare professionals' innovative behavior and patient satisfaction

Abstract: BackgroundA rare disease is a pattern of symptoms that afflicts less than five in 10,000 patients. However, as about 6,000 different rare disease patterns exist, they still have significant epidemiological relevance. We focus on rare diseases that affect multiple organs and thus demand that multidisciplinary healthcare professionals (HCPs) work together. In this context, standardized healthcare processes and concepts are mainly lacking, and a deficit of knowledge induces uncertainty and ambiguity. As such, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…diseases most often require complex multidisciplinary treatment 10 . The development of orphan drugs is often left aside in relation to other drugs with higher demand on the market.…”
Section: The Characteristics Of Rare Diseases and Their Relevance To mentioning
confidence: 99%
See 1 more Smart Citation
“…diseases most often require complex multidisciplinary treatment 10 . The development of orphan drugs is often left aside in relation to other drugs with higher demand on the market.…”
Section: The Characteristics Of Rare Diseases and Their Relevance To mentioning
confidence: 99%
“…Another issue is the existence of cohabitation in isolated communities. Likewise, the variability of symptoms and therapeutic options makes it difficult or even impossible to develop standardized protocols and guidelines 10 .…”
Section: Ethical Framework For Approaching the Rare Diseasesmentioning
confidence: 99%
“…The authors reported a high internal consistency as well as a good reliability; convergent validity was found to be satisfactory. In addition, it has been utilized in a number of studies, for example, to evaluate medical care (Clever, Jin, Levinson, & Meltzer, 2008;Hannemann-Weber, Kessel, Budych, & Schultz, 2011;Hojat et al, 2011;Zickmund, Hillis, Barnett, Ippolito, & LaBrecque, 2004).…”
Section: Patient Satisfaction In German-speaking Countriesmentioning
confidence: 99%
“…Innovative job performance may realize new ideas and generate novel, or patient‐centered solutions to improve the quality of long‐term care (Hannemann‐Weber et al. ; Xerri ). Moreover, innovative job performance concerns the implementation of new techniques or instruments to enhance clinical outcomes (Thune and Mina ).…”
mentioning
confidence: 99%
“…Although meeting the job requirements is essential for healthcare professionals, a balance is required between using rules and processes to co-ordinate the organizational tasks and giving them the flexibility to adapt to problems (For es and Camis on 2016). Innovative job performance may realize new ideas and generate novel, or patient-centered solutions to improve the quality of long-term care (Hannemann-Weber et al 2011;Xerri 2013). Moreover, innovative job performance concerns the implementation of new techniques or instruments to enhance clinical outcomes (Thune and Mina 2016).…”
mentioning
confidence: 99%